PENGARUH LINGKUNGAN SEKOLAH DAN PENDAPATAN ORANG TUA TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI SMA NEGERI 5 SOLOK SELATAN - Mukhlas, Syevri; Wahyuni, Sri; areva, Desi (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ Based on the true class XI SMA N 5 South Solok , researchers found that the problem of low economic study results , it can be seen from the value of the final semester of the 2012-2013 school year 2 students . The purpose of this study is to see how the influence of the school environment and income of parents of class XI student learning outcomes in SMA N 5 South Solok .This type of research is a quantitative study . The study population was a class XI student of SMA Negeri 5 South Solok , amounting to 182 people , while a sample of as many as 125 people by using a sampling technique is by using Slovin formula . Shaped instrument used was a questionnaire .Data analysis techniques to test the research hypothesis is the t test and F test results showed the results of hypothesis testing that the school environment is a significant and positive impact on student learning outcomes . This can be proved by the results of research which states that indigo Sig of 0.000 < Î± = 0.05 , this means that the better the school environment will impact the higher the student learning outcomes , and vice versa if the school environment is bad or not good then the results student learning will also be low .As well as the parents income is significantly and positively impact on student learning outcomes . This can be proved by the results of research that states that the Sig of 0.000 < Î± = 0.05 , this means that the higher the income of the parents will impact the higher the student learning outcomes , and vice versa if low income parents the learning outcomes students will also be low . Based on data analysis and hypothesis testing with the F test has been carried out in this study were obtained Sig 0.000 < Î± = 0.05 . This suggests that the school environment and parents income significantly and positively impact on student learning outcomes . The better the school environment and parents income the higher the student learning outcomes .Â